Galven, Nur Durriyah win DRB Hicom TSM Golf - The Edge, Financial Daily (The Edge, 2015)
Shah Alam: Selangor and national golfer Galven Kendall Green retained the DRB-Hicom Tan Sri Muhyiddin (TSM) Golf Challenge for the second successive year.